1957
DOI: 10.1111/j.1751-0813.1957.tb14694.x
|View full text |Cite
|
Sign up to set email alerts
|

The Value of the Organic Phosphorus Insecticides Malathion and Diazinon for the Protection of Sheep Against Body STRIKE.1

Abstract: Controls 10 11 13 12 10 12 12 References Fiedler, 0. G . H. and du Toit, R. (1956)-0nder-stepoort J . vek. Sci., 27: 77. Riches, J. H. and O'Sullivan, P. J. (1955)-Aust. vet. J., 31: 258. du Toit, R. and Fiedler, 0. G. H. (1953)-Onderstepoort J . vet. Sci., 26: 65. du Toit, R. and Fiedler, 0. G . H. (1954)-0ndel--stepoort J . v e t . Sci., 26: 405. (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1957
1957
1973
1973

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Further, Riches and O'Sullivan (1957) have shown that although Malathion does not protect sheep against blowflies f o r quite as long as Aldrin and Dieldrin, Diazinon protects them f o r a longer period.…”
Section: Discussionmentioning
confidence: 97%
“…Further, Riches and O'Sullivan (1957) have shown that although Malathion does not protect sheep against blowflies f o r quite as long as Aldrin and Dieldrin, Diazinon protects them f o r a longer period.…”
Section: Discussionmentioning
confidence: 97%
“…A t higher concentrations Aldrin and Dieldrin were superior to DDT and RIIC. Riches et al (1957) showed Malathion a t 0.05%, 0.1% and 0.25% gave dficicnt protection for 7, 8, 9 and 10 weeks r(ymtive'1y. Aldrin and Dieldrin at similar eonccntrations were effective for 11-18 weeks.…”
Section: Insectary Testsmentioning
confidence: 91%
“…du Toit andFiedler (1953 ancl 1954) used numerous insecticides, inclnding dieldrin, by soaking the fleece to the skin in a manner similar to jetting; Wright ei a1 (loc cit) used dieldrin, diazinoii, alilrin and B.H.C. by both jetting and surface spraying, while Riches and O'Sullivan (1957) used dieldrin, diazinon, aldrin and malathion by jetting to the skin. Most of these artificial methods rely upon the establishment of flystrike 311 the body wool of the sheep and the measure of the difference between the results of protection against artificially induced bocly strike and those of pi*otection against crutch strike in the ticld can be seen by comparing the results of Riches ancl O'Sullivan (loc c i t ) , who observed a protection period of 16-18 weeks against artificially induced body strike given by jetting with 0.02% w/v diazinoii and those of Skerman & Pryor (1957), who observed 6 weeks protection against crutch strike in the field by jetting with thc same strength of diazinon (0.02% w/v).…”
Section: Introductionmentioning
confidence: 99%